Integrated Metabarcoding and Culturomic-Based Microbiome Profiling of Rice Phyllosphere Reveal Diverse and Functional Bacterial Communities for Blast Disease Suppression - Sahu, Kuleshwar Prasad; Patel, Asharani; Kumar, Mukesh; Sheoran, Neelam; Mehta, Sahil; Reddy, Bhaskar; Eke, Pierre; Prabhakaran, Narayanasamy; Kumar, Aundy (Frontiers in Microbiology, 2021)
Phyllosphere- the harsh foliar plant part exposed to vagaries of environmental and climatic variables is a unique habitat for microbial communities. In the present work, we profiled the phyllosphere microbiome of the rice plants using 16S rRNA gene amplicon sequencing (hereafter termed metabarcoding) and the conventional microbiological methods (culturomics) to decipher the microbiome assemblage, composition, and their functions such as antibiosis and defense induction against rice blast disease. The blast susceptible rice genotype (PRR78) harbored far more diverse bacterial species (294 species) than the resistant genotype (Pusa 1602) that showed 193 species. Our metabarcoding of bacterial communities in phyllomicrobiomerevealed the predominance of the phylum, Proteobacteria, and its members Pantoea, Enterobacter, Pseudomonas, and Erwinia on the phyllosphere of both the rice genotypes. The microbiological culturomics validation of metabarcoding-taxonomic annotation further confirmed the prevalence of 31 bacterial isolates representing 11 genera and 16 species with the maximum abundance of Pantoea. The phyllomicrobiome associated bacterial members displayed antifungal activity on rice blast fungus, Magnaporthe oryzae by volatile and non-volatile metabolites. Upon phyllobacterization of rice cultivar PB1, the bacterial species such as Enterobacter sacchari, Microbacterium testaceum, Pantoea ananatis, Pantoea dispersa, Pantoea vagans, Pseudomonas oryzihabitans, Rhizobium sp., and Sphingomonassp. elicited defense response and contributed to the suppression of blast disease. qRT-PCR-based gene expression analysis enhanced expression of defense-associated genes such as OsCEBiP, OsCERK1, and phytohormones associated genes such as OsPAD4, OsEDS1, OsPR1.1, OsNPR1, OsPDF2.2, and OsFMO in phyllobacterized rice seedlings. The phyllosphere bacterial species showing blast suppressive activity on rice were tested non-plant pathogenic in tobacco infiltration assay. Our comparative microbiome interrogation of the rice phyllosphere culminated in the isolation and identification of agriculturally significant bacterial communities for blast disease management in rice farming through phyllomicrobiome engineering in the future.